EFEKTIVITAS PENEGAKAN HUKUM TERHADAP PEREDARAN ROKOK TANPA PITA CUKAI DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 39 TAHUN 2007 TENTANG CUKAI - Waloyo, Waloyo; DM , M. Yusuf; Pardede, Rudi (JOURNAL EQUITABLE, 2025)
The circulation of cigarettes without excise stamps in Indonesia has become a serious issue impacting state revenue and public health. Illegal cigarettes reduce state income and create injustice in the taxation sector. Law enforcement against illegal cigarette circulation faces challenges such as low public awareness and weak supervision. This study aims to analyze the legal provisions regarding the imposition of excise on cigarettes under Law No. 39 of 2007 and evaluate the effectiveness of law enforcement against the circulation of cigarettes without excise stamps. The research method used is normative legal research with a descriptive-analytical approach, examining regulations and related literature. The findings show that despite the existence of excise regulations, the circulation of illegal cigarettes remains high due to significant price differences between legal and illegal cigarettes. Law enforcement is still limited by a lack of resources, low legal awareness, and insufficient coordination among institutions. The study recommends regulatory evaluation, enhancing the capacity of law enforcement agencies, and promoting active public participation in combating illegal cigarettes.